THE MODEL DEVELOPMENT FOR EFFECTIVE PLANNING OF ENTERPRISE EXTENSION - Mykhaylova, T. F.; Karavaieva, M. S. (Science and Transport Progress, 2010)
The model of effective expansion of the enterprise production by using econometric modeling and dynamic programming is built.